Active extensional tectonics along the Mirabello Gulf – Ierapetra Basin depression (Eastern Crete, Greece) - Soukis, K.; Lozios, S.; Vassilakis, Emm.; Antoniou, V.; Laskari, S (EGU General Assembly 2023, 2023)
The present-day geotectonic regime of Crete Island is mainly controlled by the processes occurring along the seismically active Hellenic subduction zone, e.g., the fast convergence between Africa - Eurasian plates (at a rate of 36 mm/yr) and the simultaneous SSW-ward retreat of the subducting slab. The result is a large south-facing orogenic wedge extending from the southern coast of Crete up to the Hellenic subduction trench to the South. Contractional structures (thrusts, folds, and duplexes) have formed in the deeper parts of the wedge and caused the thickening of the crust. This has led to substantial regional uplift and extension of the upper part of the wedge. Hence, two significant arc-parallel and arc-normal sets of active normal faults crosscut the Cretan mainland, affecting the entire alpine nappe pile. These faults have created a characteristic basin and range topography expressed through impressive E-ESE and N-NNE horst and graben structures bounded by fault zones with segments ranging from 5 to more than 20 km. Detailed fault mapping of the Mirabello Gulf – Ierapetra Basin depression revealed a dominant NNE-SSW fault system, occupying the central and northern part, and a subordinate E-W to ESE-WNW system, observed mainly along the southern coastal zone. In the ESE margin, the deformation is localized mainly along the 30 km long NNE-SSW Kavousi – Ieraptera fault zone. On the other hand, in the WNW margin, the deformation is distributed in a larger population of relatively minor faults, organizing in more complex second-order horst and graben structures. In the southern part of the Ierapetra Basin, the E-W to ESE-WSW faults are significantly less and concern 2-3 specific zones. Specific morphological structures such as the remarkable range high, the deep V-shaped gorges, the large scree thickness, and the prominent post-glacial fault scarps produced along the basin margins indicate the intensive activity of these faults during the Quaternary. The NNE-SSW fault system seems to be younger and more active, given that i) intersects the E-W or ESE-WNW faults of the southern part, ii) produces significant fault scarps and polished fault surfaces in the cemented scree along the fault zone, and iii) kinematically is compatible with the recent and present-day focal mechanisms (e.g., the 2021 Arkalochori earthquakes). In conclusion, the Ierapetra Basin has formed and developed through an overall E-W extension parallel to the present-day geometry of the arc.